Tomamos $x, y \in \mathbb{R}$ .
Entonces yo digo :
$\mid \sqrt{(1+x^2)} - \sqrt{(1+y^2)} \mid$ $\le$ $\mid 1+\sqrt{x^2} - 1-\sqrt{y^2} \mid$
$\Leftrightarrow$ $\mid \sqrt{(1+x^2)} - \sqrt{(1+y^2)} \mid$ $\le$ $\mid \sqrt{x^2} - \sqrt{y^2} \mid$
$\Leftrightarrow$ $\mid \sqrt{(1+x^2)} - \sqrt{(1+y^2)} \mid$ $\le$ $\mid \mid{x} \mid - \mid{y} \mid \mid$
$\Leftrightarrow$ $\mid \sqrt{(1+x^2)} - \sqrt{(1+y^2)} \mid$ $\le$ $\mid \mid{x} \mid - \mid{y} \mid \mid$ $\le$ $\mid x-y \mid$
Lo que significa que $k=1$ ?
Así que $f$ no es un mapa de contracción. ¿Funciona? Gracias de antemano.